2019
DOI: 10.5114/pjp.2019.82905
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations in BRCA1&2 in 201 unselected ovarian carcinoma samples – single institution study

Abstract: Ovarian cancer (OC) is the most lethal among gynecologic malignancies worldwide. Unfortunately, in around 70% of cases cancer is diagnosed in late stages (III-IV) which decreases the 5-year survival rate to 25%. The standard of care in ovarian cancer is debulking surgery followed by chemotherapy regimens based on platinum salts. Since 2014 PARP inhibitors became available for OC patients with germline or/and somatic mutations in BRCA1/2, including maintenance therapy. BRCA1/2 Next Generation Sequencing (NGS)-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…The overall prevalence of BRCA1/2 PV in 570 HGSC tumor samples was 16%. While consistent with the 17% reported in a recently published large cohort, [14] it is somewhat lower than the 24–30% reported by others [15,18,31,32]. This is potentially a reflection of the large‐scale, population‐based testing approach represented in our study compared with small, controlled research‐based settings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The overall prevalence of BRCA1/2 PV in 570 HGSC tumor samples was 16%. While consistent with the 17% reported in a recently published large cohort, [14] it is somewhat lower than the 24–30% reported by others [15,18,31,32]. This is potentially a reflection of the large‐scale, population‐based testing approach represented in our study compared with small, controlled research‐based settings.…”
Section: Discussionsupporting
confidence: 90%
“…[7,10,11] However, the introduction of PARPi in the treatment of HGSC is rapidly changing the landscape of BRCA1/2 testing. While the prevalence of germline BRCA1/2 PV is reported to be 10-20% in women with HGSC [12,13], BRCA1/2 PVs are identified in 15-30% of tumor samples [14][15][16][17][18][19]. The difference, representing individuals with somatic variants present only in tumor tissue, accounts for an important cohort of patients who could benefit from PARPi therapy, but who would not be identified by germline testing alone.…”
Section: Introductionmentioning
confidence: 99%
“…When tumor testing is completed, follow-up genetic counseling and germline testing of patients with identified PVs is critical to clarify whether family members may be at risk. This is particularly important for HGSOC, as 57-85% of BRCA1/2 PVs identified in tumor tissues are germline in origin [25,[33][34][35]. In this study, 94% (16/17) of HGSOC patients with a BRCA1/2 PV in their tumor were referred for genetic counseling, all of whom provided a blood sample for germline testing.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we identified one somatic variant in a tissue with 35% of tumor cells (Table 3), which is slightly lower but still in concordance with the data of other groups. Kowalik et al reported that the lowest percentage of tumor cells with detectable pathogenic variants was 40% in ovarian cancer tissue samples [51], while Ellison et al suggested that the starting material should contain at least 10% of tumor cells in order to detect low-frequency somatic variants [52].…”
Section: Discussionmentioning
confidence: 99%